Koperasi sebagai Katalisator Pengentasan Kemiskinan: Pendekatan Metode Ganda - Azhari Azhari (Jurnal Simki Economic, 2026)
Cooperatives in Indonesia, numbering in the hundreds of thousands and comprising tens of millions of members, are anticipated to play a significant role in mitigating classic socioeconomic challenges, such as poverty, faced by the country. This study aims to investigate the role of cooperatives in poverty alleviation using a dual-methodological approach, specifically employing Data Envelopment Analysis (DEA) to assess cooperative productivity and panel regression to evaluate its impact on poverty levels. The research utilizes secondary data, which encompasses internal capital, external capital, business volume, residual cooperative business results, and poverty levels in Indonesia. The findings indicate that cooperatives in Indonesia have not exhibited optimal productivity in their management practices. Nonetheless, the productivity of cooperatives plays a significant role in facilitating poverty reduction. These results suggest that cooperatives, when effectively managed, can function as a potent instrument for socio-economic empowerment. The implications of this study underscore the necessity for policies that bolster the strengthening of cooperatives, particularly in relation to managerial capabilities, access to financing, and market accessibility, to enhance their efficacy in poverty reduction. Future research should integrate qualitative methodologies and long-term analyses to further explore the social factors influencing the success of cooperatives within a broader framework.